Effect of trust, quality of service and product quality on consumer loyalty in CV. Naisha Madu Nusantara - Boby Gustionto; Librina Tria Putri; Muhammad Salis (STIE Bangkinang Publishing, 2022)
This study aims to determine the effect of trust, service quality and product quality on consumer loyalty at CV. Naisha Madu Nusantara in Pekanbaru. The analysis used in this study is multiple linear analysis using SPSS Version 25 with a total sample of 96 respondents. Hypothesis testing was carried out using a simultaneous test (f test) and a partial test (t test). Based on the results of the study, it can be concluded that simultaneously and partially trust, service quality and product quality affect consumer loyalty at CV. Naisha Madu Nusantara Pakanbaru. The close relationship between the independent variable and the dependent variable is very strong with the contribution of the independent variable to the dependent variable of 78.40%. While the remaining 21.60% is determined by other variables not included in this study.